Argumentation Theory: A Pragma-Dialectical Perspective - Eemeren, Frans H. van (Springer, 2018)
Argumentation theory is a prospering discipline, with book series, academic journals and worldwide big general conferences and more focused smaller conferences, symposiums and research colloquiums. There is also a comprehensive Handbook of Argumentation Theory that provides an up-to-date overview of the variety of theoretical approaches to argumentation that have contributed to the current state of the art. A short introduction to the theorizing that takes place in the discipline however is harder to find. This book is written with the intention to fill this gap. An extra motive for me to write this book is that an introduction into the theory of pragma-dialectics, the theoretical approach to argumentation I have helped to create since the 1970s, is also lacking. The insights developed in the various components of the theoretical framework of this theory have been explained in a number of separate monographs but an overview of how they hang together is not so easy to be gained. This is why I decided to try to combine the fulfilment of the two demands by writing an introduction into argumentation theory in which the discipline is viewed from a pragma-dialectical perspective. Argumentation Theory: A Pragma-Dialectical Perspective provides a general introduction into argumentation theory, but it explains the theorizing about argumentation in a pragma-dialectical way. This means that great emphasis is put both on the pragmatic dimension of argumentation as a goal-directed verbal activity and on its dialectical dimension as part of a critical exchange aimed at resolving a difference of opinion. An advantage of choosing this approach is that in this way a clear and coherent overview can be presented of what argumentation theory involves. Another advantage is that it gives me the opportunity to explain systematically in this theoretical complement of Argumentation: Analysis and Evaluation, the practical textbook I co-authored with Francisca Snoeck Henkemans, the connections between the various components of the pragma-dialectical theory.